Do match ao date: a tensão entre o medo, o desejo e a vergonha em mulheres que buscam relacionamentos com homens pelo Tinder em Santa Maria - RS - Carvalho, Carolina Adolfo de (2019)
For just over a decade, companies have invested in social networking sites and applications and have turned flirting into something more discreet and private, while providing their users a broader desire management. Thinking about it, this work wants to debate the perspective that the same technology that made real the free exercise of flirting, also started to raise new fears in its users, especially among women. Based on an ethnographic inquiry undertaken from participant observation and interviews with women users of the dating app Tinder in Santa Maria-RS, and also in dialogue with theories which deal with emotions, digital media and urban legends, I propose a reflection on whether there is, and how it happens, a tension between fear, desire and shame in the searches of these women for partners in the application. I discuss these sociabilities considering that these women live in a society in which gender violence, especially domestic violence, practiced by close harassers, is a reality widely spread in media. I have identified throughout the fieldwork that these women feel more comfortable flirting with the application, but they still suffer from the stigma of taking initiative to search for a partner. Furthermore, influenced by the mediatization of violence, they fear being victims of the legendary figure of the Internet psychopath, broadly exploited by news and cinema, even though statistics show that the perpetrator of women in Brazil is, in the great majority of cases, a known man of the victim. This fear hampers the relationships of these women with men they know on the application and troubles them to take a number of precautions before leaving for the face-to-face date, strongly influencing their sociabilities inside and from the tool.